Assessment of the effect of silica calcium phosphate nanocomposite on mesenchymal stromal cell differentiation and bone regeneration in critical size defect - Shams Altwaim; Mohammed Al-Kindi; Nihal AlMuraikhi; Sarah BinHamdan; Ahmad Al-Zahrani (Saudi Dental Journal)
Objective: The research was designed to assess silica calcium phosphate nanocomposite (SCPC) biocompatibility and bioactivity as an osteoinductive scaffold and cell carrier. Consequently, the ability of cell seeded SCPC implant to regenerate a critical size defect in rat calvarium. Materials and Methods: The study was conducted in two parts. A series of in vitro experiments on bone marrow stromal cells (MSCs) seeded in the SCPC scaffold evaluated cell attachment, proliferation and osteogenic differentiation. In the second part, a cell seeded SCPC construct was implanted in rat calvarium and bone regeneration was assessed by histological examination to evaluate the newly formed bone quality and the residual graft volume. Results: In vitro experimentation revealed that MSCs cultured on SCPC maintained viability and proliferation when seeded into the SCPC. Scanning electron microscopy demonstrated cell adhesion and calcium appetite formation, MSCs differentiated towards the osteogenic lineage as indicated by the upregulation of RUNX2, ALP, Col1a1 markers. Histological examination showed regeneration from the periphery and core of the defect with new bone formation at different stages of maturation. Conclusion: Regenerative medicine delivers promising solutions and technologies for application in craniofacial reconstruction. SCPC scaffold has the potential to be used as a cell carrier to achieve stem cell-based bone regeneration, which provides a viable alternative for treatment of challenging critical size defect.